2005
DOI: 10.1128/jb.187.15.5278-5291.2005
|View full text |Cite
|
Sign up to set email alerts
|

Use of Suppression-Subtractive Hybridization To Identify Genes in the Burkholderia cepacia Complex That Are Unique to Burkholderia cenocepacia

Abstract: We have previously shown differences in virulence between species of the Burkholderia cepacia complex using the alfalfa infection model and the rat agar bead chronic infection model. Burkholderia cenocepacia strains were more virulent in these two infection models than Burkholderia multivorans and Burkholderia stabilis strains. In order to identify genes that may account for the increased virulence of B. cenocepacia, suppression-subtractive hybridization was performed between B. cenocepacia K56-2 and B. multiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
25
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 71 publications
(101 reference statements)
1
25
0
Order By: Relevance
“…We also observed that BCAM0224 is an exclusive marker of epidemic B. cenocepacia belonging to the ET-12 lineage and we therefore recommend employment of this PCR assay for discrimination of bacteria among Bcc members that belong to this virulent subgroup. These results are compatible with previous studies, which revealed the autotransporter adhesins BCAM0223 and BCAM0225 as unique in the ET-12 lineage (Bernier & Sokol, 2005), but BCAM0223, just like cblA, is present in some B. cenocepacia strains distinct from ET-12 (Turton et al, 2009).…”
Section: Discussionsupporting
confidence: 82%
“…We also observed that BCAM0224 is an exclusive marker of epidemic B. cenocepacia belonging to the ET-12 lineage and we therefore recommend employment of this PCR assay for discrimination of bacteria among Bcc members that belong to this virulent subgroup. These results are compatible with previous studies, which revealed the autotransporter adhesins BCAM0223 and BCAM0225 as unique in the ET-12 lineage (Bernier & Sokol, 2005), but BCAM0223, just like cblA, is present in some B. cenocepacia strains distinct from ET-12 (Turton et al, 2009).…”
Section: Discussionsupporting
confidence: 82%
“…The loss of hopanoid production and the resulting compromise in the structural integrity of the membrane may affect other structures within or spanning the cell envelope. B. cenocepacia relies on membrane-spanning polar flagella for swimming motility, a form of movement regulated by individual cells perceiving chemical signals, which can be measured using characteristic swim agar plates (3,35). Upon sensing the proper environmental signals, B. cenocepacia modifies its cell morphology to become an elongated, multiflagellated swarm cell (3,24,35).…”
Section: Resultsmentioning
confidence: 99%
“…B. cenocepacia relies on membrane-spanning polar flagella for swimming motility, a form of movement regulated by individual cells perceiving chemical signals, which can be measured using characteristic swim agar plates (3,35). Upon sensing the proper environmental signals, B. cenocepacia modifies its cell morphology to become an elongated, multiflagellated swarm cell (3,24,35). Swarming motility is a coordinated social behavior, allowing the bacteria to act as a multicellular population to rapidly colonize nutrient-rich solid substrates, such as swarm agar plates (21,22,43,63).…”
Section: Resultsmentioning
confidence: 99%
“…One approach to identify such virulence factors is to identify genes present in virulent F. tularensis that are absent or have low homology to genes in closely related F. novicida. SSH has been used to successfully identify virulence genes present in pathogens that are absent in closely related species (Bernier & Sokol, 2005;DeShazer et al, 2001;Harakava & Gabriel, 2003;Liu et al, 2003;Newton et al, 2006;Parsons et al, 2003;Winstanley, 2002), and was therefore used to identify genes uniquely expressed by the more virulent type A and B strains. Seventy-six LVS-specific genes with hypothetical or known functions were identified in eight genomic regions in multiple SSH clones (Ahmed & Inzana, 2004).…”
Section: Discussionmentioning
confidence: 99%